NECROTISING INFUNDIBULOHYPOPHYSITIS: A RARE CAUSE OF CENTRAL DIABETES INSPIDUS: NECROTISING INFUNDIBULOHYPOPHYSITIS: A RARE CAUSE OF CENTRAL DIABETES INSPIDUS - Kapur, Atul; Sethi, Arshia Kaur; Kapoor, Aprajita; Mahajan, Goldaa; Gupta, Ajay (Indian Journal of Case Reports, 2022)
Diagnosis of central diabetes inspidus (CDI)requires a high index of clinical suspicion especially in patients with traumatic brain injury or following neurosurgery. We would like to report a rare case of necrotising infundibulohypophysitis(NIH)  in a young male with CDI and discuss the radiological findings and differential diagnosis.